FORMULASI METODE STUDI ISLAM ANTARA KRITIK DAN TAWARAN - M. Agus Kurniawan (Insititut Agama Islam Agus Salim Metro Lampung, 2023)
A change of paradigm (shifting paradigm) of dichotomous-atomistic toward integrative paradigm bidinterkonektif, interconnectivity and sensitivity between different disciplines need to obtain a priority basis and need to be built and developed. In other words the need to foster the scientific ethos that emphasizes interdisiplinary, sensitivity and interconnectivity between various public and religious disciplines. As above of the various approaches of science the science of psychology, philosophy, sociology, anthropology, and phenomenology used to approach religion separately, then it is the time approaches interdisiplinary, interconnectivity, and sensitivity interdisciplinary Such a view underlined the importance of the framework which was built in the fundamentals of the doctrine and the fundamental value that is contained in the Quran and al-Sunnah as the principal source